Perception of teaching history and epistemological conceptions. Research with future teachers - Gómez Carrasco, Cosme J.; Rodríguez Pérez, Raimundo A.; Mirete Ruiz, Ana Belén (Revista Complutense de Educación, 2017)
The teaching methods used in history classroom is an axis of research key to understanding the historical education of the students and their conceptions of this subject and the training opportunities. In the last two decades there have been many works internationally (both in Ibero-America and Anglo-Saxon) with important proposals on history education. In these works it insisted on the need to change the methods, techniques and resources used by teachers in the classroom. The aim of this paper is to analyze the memories of teacher in training about teaching methodology used in history classroom, and their epistemological conceptions. The sample is 293 students of the Degree in Primary Education from the University of Murcia (Spain). For the collection of information has been developed and validated by experts a questionnaire with a Likert rating scale. Data encryption have been in the SPSS v.19.0 statistical package for further analysis. The results show the persistence of a traditional methodology in teaching history and contradictions in the epistemological conceptions about this subject in future teachers.
Keywords: history education; teaching methods; epistemology; teacher training